A survey on emerging issues in interconnection networks. (16th February 2021) - Moudi, Mehrnaz; Othman, Mohamed
Nowadays, the interconnection network is considered as an important architectural choice for the future parallel system in many processors owing to the scalable nature of the interconnection network. The basic idea of interconnection is to reach efficient network communication and overcome scalability problems. Since an interconnection network plays a critical role in such computers, with millions of processors providing an efficient data transferring in the possible shortest time without congestion, designing various topologies for these networks is of high significance. This survey paper focuses on the issues emerged during the design of enhanced interconnected topologies to provide efficient inter-processor communication considering a maximum number of transferred packets in the shortest path.